PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA PADA PT. SINARMAS MULTIFINANCE. - Fen ny; Cut Fitri Rostina; Hendra Nazmi; Inta nia; Vin cent (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2019)
Leadership style and compensation are elements that can influence job satisfaction in order to improve employee job satisfaction. This study aims to determine and analyze the influence of leadership style and compensation on employee job satisfaction at PT. Sinarmas Finance Medan. This type of research is  explanatory  research.  The  entire  population  is  sampled  in  the  study. Information retrieval of 123 employees who acted as respondents in the study was conducted using a questionnaire composed of five Likert scales. Data analysis using multiple linear regression analysis and coefficient of determination and simultaneous tests and partial tests. The results showed that leadership and compensation styles partially or simultaneously had a positive and significant effect on employee job satisfaction at PT. Sinarmas Finance Medan. Based on the results of this study, the implications for management are to increase employee confidence in leadership and work motivation of employees so that it can improve employee job satisfaction and achieve university goals